Education on Social Stigma Toward Pulmonary Tuberculosis Patients to Enhance Environmental Support - Rahmad Gurusinga (JURNAL PENGMAS KESTRA (JPK), 2026)
Pulmonary tuberculosis (TB) remains a public health problem in Indonesia that requires comprehensive treatment. In addition to medical factors, social stigma against TB sufferers is a major obstacle in disease control efforts. Stigma can hinder early detection, decrease treatment adherence, and reduce support from the surrounding community. This community service activity aims to increase public knowledge and reduce stigma through health education to strengthen support for TB sufferers. The methods used were interactive lectures, discussions, and leaflet distribution to 18 participants consisting of patient families, health cadres, and the general public in the Sialang Buah Community Health Center (Puskesmas) working area. Evaluation was conducted using pre-tests and post-tests to measure changes in knowledge levels. The results showed an increase in the average knowledge score from 62 before the intervention to 84 after the intervention. The percentage of participants with good knowledge increased from 22% to 72%, while the percentage with poor knowledge decreased from 28% to 6%. Furthermore, there was a change in participants' attitudes, becoming more positive, empathetic, and supportive of TB sufferers. This demonstrates the important role of health education in increasing understanding and reducing social stigma in the community. In conclusion, health education is an effective strategy to support TB control by increasing public knowledge and changing attitudes. Ongoing community-based education is recommended to maintain the achieved results.